MISKONSEPSI SISWA PADA MATERI OPERASI HITUNG BENTUK ALJABAR DI KELAS VII SMP KEMALA BHAYANGKARI - Rullianti, Rullianti; Sakidin, Sugiatno; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMathematical communication skills are contained in Minister of Education and Culture Regulation (Permendikbud) Number 20 of 2016 concerning Competency Standards for Primary and Secondary Education Graduates. Through mathematical communication skills students can explain mathematical concepts in the form of numbers, images and or symbols using oral and written communication. That is, mathematical communication skills needed by students to be able to communicate their conceptual understanding. Instead, conceptual understanding is needed by students to be able to communicate mathematically. This study aims to describe the mathematical communication skills studied from the conceptual understanding of class VIII students at SMPN 12 Sungai Ambawang Kab. Kubu Raya, West Kalimantan Province. The research method used is descriptive in the form of case studies. Retrieval of data using tests and interviews. The subjects in this study consisted of 27 students who were divided into high, medium and low conceptual understanding levels. The results of data analysis show that students with high conceptual understanding have good mathematical communication skills. Students with conceptual understanding are having good mathematical communication skills. Students with low conceptual understanding have poor mathematical communication skills.Â Â Keywords: Mathematics Communication, Conceptual Understanding, SetÂ